Distinct usage of three C-type lectins by Japanese encephalitis virus: DC-SIGN, DC-SIGNR, and LSECtin - Shimojima, Masayuki; Takenouchi, Atsushi; Shimoda, Hiroshi; Kimura, Naho; Maeda, Ken (Archives of virology, 2014)
Infection with West Nile virus and dengue virus, two mosquito-borne flaviviruses, is enhanced by two calcium-dependent lectins: dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN), and its related molecule (DC-SIGNR). The present study examined the relationship between Japanese encephalitis virus (JEV) infection and three lectins: DC-SIGN, DC-SIGNR, and liver sinusoidal endothelial cell lectin (LSECtin). Expression of DC-SIGNR resulted in robust JEV proliferation in a lymphoid cell line, Daudi cells, which was otherwise non-permissive to infection. DC-SIGN expression caused moderate JEV proliferation, with effects that varied according to the cells in which JEV was prepared. LSECtin expression had comparatively minor, but consistent, effects, in all cell types used in JEV preparation. While DC-SIGN/DC-SIGNR-mediated JEV infection was inhibited by yeast mannan, LSECtin-mediated infection was inhibited by N-acetylglucosamine β1-2 mannose. Although involvement of DC-SIGN/DC-SIGNR in infection seems to be a common characteristic, this is the first report on usage of LSECtin in mosquito-borne flavivirus infection.